Counselling low-back-pain patients in secondary healthcare: a randomised trial addressing experienced workplace barriers and physical activity. Issue 1 (19th May 2011) - Jensen, Lone Donbæk; Maribo, Thomas; Schiøttz-Christensen, Berit; Madsen, Finn Hjorth; Gonge, Bigitte; Christensen, Michael; Frost, Poul
Abstract : Objective: To assess if counselling by an occupational physician (OP) addressing experienced workplace barriers and physical activity integrated as a part of low-back pain (LBP) outpatient treatment influences pain, function and sick leave. Methods: Randomised controlled trial in the secondary healthcare sector with 3 months' follow-up. The participants were LBP patients who, independently of sick-leave status, expressed concerns about the ability to maintain their current job. Patients referred for surgery were excluded. The intervention consisted of two counselling sessions conducted by an OP addressing both workplace barriers and leisure-time physical activity. A workplace visit was performed if required. Pain, function and duration of sick leave due to LBP were primary outcomes. Results: A reduction in bodily pain and improvement in physical function both measured by the 36-item short-form health survey questionnaire in favour of the intervention group was found. The change in pain score was found to be clinically relevant. The risk of sick leave for at least 8 weeks due to LBP was significantly reduced in the intervention group. Two secondary outcomes, Fear Avoidance Beliefs about physical activity and maximum oxygen uptake, supported compliance and adherence to the part of the intervention focusing on enhanced physical activity. Conclusion: Two short counselling sessions by an OP combining advice on meeting workplace barriers and enhancing physical activity had a substantial effect on important prognostic factors for LBP patients with moderate to severe symptoms diagnosed in outpatient rheumatological clinics. Trial registration: Current Controlled Trials ISRCTN13071157